2018
DOI: 10.1007/s00167-018-5004-5
|View full text |Cite
|
Sign up to set email alerts
|

Steeper posterior tibial slope correlates with greater tibial tunnel widening after anterior cruciate ligament reconstruction

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Some total knee arthroplasty (TKA) studies have indicated that an appropriate posterior slope component would improve the flexion angle (Arabori et al, ; Bellemans, Banks, Victor, Vandenneucker, & Moemans, ; Malviya, Lingard, Weir, & Deehan, ; Massin & Gournay, ). Thus, a better understanding of the factors relevant to the PTS would help to improve anterior cruciate ligament reconstruction, high tibial osteotomy, and TKA (Kuriyama et al, ; Nagai et al, ; Nha, Kim, Ahn, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some total knee arthroplasty (TKA) studies have indicated that an appropriate posterior slope component would improve the flexion angle (Arabori et al, ; Bellemans, Banks, Victor, Vandenneucker, & Moemans, ; Malviya, Lingard, Weir, & Deehan, ; Massin & Gournay, ). Thus, a better understanding of the factors relevant to the PTS would help to improve anterior cruciate ligament reconstruction, high tibial osteotomy, and TKA (Kuriyama et al, ; Nagai et al, ; Nha, Kim, Ahn, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…26 In our study, we also noted an association between posterior tibial slope and tunnel size as has been demonstrated by prior authors. 27 Although the clinical relevance of the very small (1.7–1.8 degrees) difference in slope is not known, it is possible that increased slope leads to increased graft load and potentially increased graft motion and risk of tunnel widening.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that increased lateral PTS results in greater TW after ACL reconstruction. 7 , 8 , 9 …”
Section: Introductionmentioning
confidence: 99%
“… 7 , 11 , 12 , 13 Therefore, the correlation between femoral and tibial TW after anatomical ACL reconstruction using BTB grafts has not been fully understood. Even among the papers that studied the relationship between PTS and TW, most examined only the effects on the tibial side of TW, 7 , 8 , 9 and the effects on the femoral side of TW have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%